PENERAPAN MODEL DISCOVERY LEARNING MELALUI PENGGUNAAN MEDIA JARING-JARING BANGUN RUANG UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV-B SDN PAKIS V SURABAYA - Wulandari, Choirummintin; Pratiwi, Desi Eka; Dini, Nanda (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2024)
This research aims to apply the discovery learning model through the use of spatial net media to improve the learning outcomes of students in class IV B SDN Pakis V Surabaya. The instruments used in this study were initial observation, teacher and learner activity observation sheets, and learner learning outcomes test (assessment) sheets. The results showed that the application of the discovery learning model through the use of media can improve the learning outcomes of students. The results of the study obtained a comparison of student learning outcomes according to the criteria for achieving learning objectives (KKTP). The achievement of learning outcomes in cycle I shows that the category has not been achieved still shows 6.89%; category achieved 17.24%; category achieved well 51.72%; category achieved very well 24.13%. The average class score was 75.82. While in cycle II showed better results where the achievement of learning outcomes was 100% with details in the achieved category 6.89%, the category achieved well 37.93% and the category achieved very well 55.17%. There are no learners who fall into the unachieved category. The average class score also increased to 85.00. Thus the application of discovery learning through the use of media nets can improve student learning outcomes.